Hukum Penetapan Mahar Oleh Sultan Selangor di Tinjau dari Hukum Islam - Hatim Bin Shaharuddin, Muhammad; Fatimah, Fatimah (UNES Law Review, 2023)
Islam has established lofty and noble goals for marriage. Islam also establishes dowry as an exclusive right for women. The dowry is a financial right that is obligatory by the prospective husband to the prospective wife. Although the dowry is an obligation of the prospective husband to the prospective wife, Islam never burdens the dowry beyond the ability of the prospective husband himself. However, what happened in Malaysia, especially in the State of Selangor, the Sultanate of Selangor issued a regulation regarding the minimum limitation of the amount of dowry in the state of Selangor, where Islam itself never gave a minimum or maximum limit to the amount of dowry. Because of this, this research aims to find out how Islamic law views the determination of the minimum amount of dowry set by the Sultanate of Selangor. With the formulation of the problem of how the implications of the Selangor Islamic Religious Office's decision on the minimum amount, how Islam views the determination of the minimum amount of dowry set by the Sultanate of Selangor. This research uses qualitative research with a juridical sociological empirical legal approach where the author focuses on research on the implementation or operation of a rule of Islamic law in society, whether it is related to the effectiveness of implementation, to the impact of its implementation on Islamic law in the structure of society. The results of the research show that the fuqaha agree that there is no maximum limit in the amount of dowry, but in the minimum limit the fuqaha differ in their opinion regarding this matter.